The Relation of Educational Level, Academic Achievement (GPA) and Depression Among Public School Adolescent - Mukhripah Damaiyanti; Dwi Rahmah Fitriani (IJNP (Indonesian Journal of Nursing Practices), 2017)
Depression is a worlwide mental health problem psychology disorder in adolescent. Depression is one of the emotional problems, hopelessness and  helplessness are its main causes. The other word, depression is aprevalent problem among college’s student ability to perform activities of daily life.  This descriptive correlation study aimed to describe the relation of educational level, academic achievement (GPA) and depression  among public school adolescents of Samarinda municipal, East Kalimantan province, Indonesia. A total of 552 adolescents in senior high school aged between 14-19 years were recruited through stratified cluster sampling. The instruments was The Center for Epidemiologic Studies Depression (CES-D). The data were analyzed by statistical method including t-test, Chi-square, and Pearson correlation. The result showed the prevalence of depression in this sample of Indonesian adolescents was 52.7%. Adolescent females showed almost equal prevalence of depression than adolescents’ males (26.6%, 26.1%), respectively. There was significant relationship between adolescents’ depression and educational level (X²= 8.039, p value= 0.018). Specifically, based on the findings suggest interventions program to reduce depression in adolescents by giving health education with specific mental health in school. Some programs are able to do in school such as counseling center, stress management program, time management, and screening about negative life events. This strategy need to include the participation of other personnel such as class coordinator and health workers to be successful of program.